Answer:
7.12
Step-by-step explanation:
The formula for the effective annual yield is given as:
i = ( 1 + r/m)^m - 1
Where
i = Effective Annual yield
r = interest rate = 7% = 0.07
m= compounding frequency = semi annually = 2
i = ( 1 + 0.07/2)² - 1
i = (1 + 0.035)² - 1
= 1.035² - 1
= 1.071225 - 1
= 0.071225
Converting to percentage
0.071225 × 100
= 7.1225%
Approximately to 2 decimal places = 7.12
Therefore, the annual effective yield = 7.12
Answer:
x = 4
Step-by-step explanation:
Given the 2 equations
2x - y = 11 → (1)
x + 3y = - 5 → (2)
Multiply (1) by 3 and add to (2) to eliminate the y- term
6x - 3y = 33 → (3)
Add (2) and (3) term by term to eliminate y, that is
7x = 28 ( divide both sides by 7 )
x = 4
<u>Answer:</u>
-10,1,19
<u>Step-by-step explanation:</u>
<u></u>
x+y+z = 10 (Equation 1)
2y-x= 12 (Equation 2)
x-y+2z = 7 (Equation 3)
(Equation 2): -x = -2y+12
x = 2y-12 (Equation 4)
(Equation 1) - (Equation 3): 2y-z = 3
-z = -2y+3
z = 2y-3 (Equation 5)
Substitute (4) and (5) into (1)
x+y+z = 10
(2y-12)+y+(2y-3) = 10
5y-15 = 10
5y = 5
y=1
Substitute y=1 into (2)
2y-x= 12
2(1)-x= 12
2-x= 12
-x= 12-2
-x= 10
x= -10
Substitute y=1 and x=-10 into (1)
x+y+z = 10
-10+1+z = 10
z-9 = 10
z = 10+9
z = 19
Order: x = -10, y = 1, and z = 19
Fx=8(20) -10
fx= 160-10
answer= 150